Customer Perceptions of Murabahah Financing on MSMEs - Muflih Khallab Al Mustaqim; Muhammad Djakfar; Misbahul Munir (AL-ARBAH: Journal of Islamic Finance and Banking, 2020)
Purpose - This study aims to examines the concept and implementation strategy of murabahah financing in the development of MSMEs and customer perceptions of murabahah financing at Bank BRI Syariah Jambi Branch Office.Method - This research uses a qualitative approach with a type of case study. The research data were obtained by conducting in-depth interviews, observation and documentation. MethodMiles and Huberman were used as data analysis techniques by way of data reduction, data presentation and drawing conclusions / verification.Result - Murabahah financing at BRI Syariah Bank Jambi Branch Office using murabahah with installments (bitsaman ajil). The next concept is to combine the wakalah and murabahah contracts. The strategy chosen in an effort to increase murabahah financing is to implement two strategies simultaneously, namely the internal strategy and the external strategy. Meanwhile, the perceptions of murabahah financing customers on the development of MSMEs are generally satisfied with the systems, regulations and services provided. However, customers' understanding of the concept of Islamic banking is still minimal.Implication - Optimizing the strategy for increasing financing and disseminating the understanding of the Islamic banking concept to customers and the general public at large.Originality- This study aims to determine the perceptions of Islamic bank customers about murabahah financing in Jambi City.